Structural and optical studies of Fe2O3 doped barium strontium titanate borosilicate glasses - Yadav A.K.; Gautam C.R. (My University, 2025)
Perovskite (Ba,Sr)TiO3 borosilicate glasses in the system 64[(Ba1-xSrx).TiO3]-30[2SiO2.B2O3]-5[K2O]-1[Fe2O3] (0.4 ≤x≥1.0) were prepared by conventional melt-quench method. Synthesized glass samples were characterized by infrared and Raman spectroscopic techniques for their structural investigations while optical properties of these glasses have been studied by using UV-Vis NIR spectroscopy. These investigations confirm the absence of boroxol ring in glassy matrix. Optical band gap of barium strontium titanate borosilicate glasses lies in the range 2.48-2.87 eV and its density has been found to be in the range 2.70-3.12 g/cc.